2015
DOI: 10.1021/ja511503d
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Metals Incorporation of a Whole Single Catalyst Particle Using Element Specific X-ray Nanotomography

Abstract: Full-field transmission X-ray microscopy has been used to determine the 3D structure of a whole individual fluid catalytic cracking (FCC) particle at high spatial resolution and in a fast, noninvasive manner, maintaining the full integrity of the particle. Using X-ray absorption mosaic imaging to combine multiple fields of view, computed tomography was performed to visualize the macropore structure of the catalyst and its availability for mass transport. We mapped the relative spatial distributions of Ni and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 15 publications
7
122
0
Order By: Relevance
“…1, the morphological information obtained by nano-TXM is displayed. The particle appears to be a typical FCC catalyst particle when compared with previous studies181920212941: it has a diameter of about 40 μm, shows a denser surface layer of 1–2 μm thickness and a complex macro-pore structure throughout the rest of the particle; the total porosity was determined to 18.8%. In this study, we additionally performed a pore throat analysis45, which revealed a pore throat size distribution peak at about 320 nm.…”
Section: Resultsmentioning
confidence: 58%
“…1, the morphological information obtained by nano-TXM is displayed. The particle appears to be a typical FCC catalyst particle when compared with previous studies181920212941: it has a diameter of about 40 μm, shows a denser surface layer of 1–2 μm thickness and a complex macro-pore structure throughout the rest of the particle; the total porosity was determined to 18.8%. In this study, we additionally performed a pore throat analysis45, which revealed a pore throat size distribution peak at about 320 nm.…”
Section: Resultsmentioning
confidence: 58%
“…Furthermore, no information about size and shape of the mesopores can be obtained because the resolution is limited. [171][172][173] Recently, Mitchell et al used synchrotron radiation X-ray tomography microscopy (SRXTM) to visualize the internal pore architecture of an industrial granule consisting of hierarchical alkaline-treated ZSM-5 zeolite and the binder attapulgite. Besides imaging porosity, the recently developed optical method based on microimaging by interference and infrared microscopy was successfully used to monitor diffusion of non-fluorescent guest molecules, such as methanol and ethanol, through nanoporous zeolites.…”
Section: Confocal Fluorescence Microscopymentioning
confidence: 99%
“…For example, B. M. Weckhuysen, et al. reported a method for investigating three‐dimensional morphology and heavy metal poisoning of individual catalyst particles for fluid catalytic cracking (FCC) using TXM‐tomography technique at multiple absorption edges and revealed the interaction of porosity and elemental distribution changes in the catalyst . J.…”
Section: Introductionmentioning
confidence: 99%